The Model of Optimal Exporter Approach to Southeast Asian Markets - Babić, Ante; Babić, Tomislav (Oeconomica Jadertina, 2017)
In this paper we are examining optimal approach to the markets of Southeast Asia. Croatian export has been traditionally oriented towards few neigboring countries. Countries of Southeast Asia on the other hand represent (besides China, Korea and Japan) market of almost 600 million inhabitants with relatively high growth rates, which is making them an interesting growth area that is less dependent on European trends. As Southeast-Asian countries are considerably remote and „exotic“ one has to deeply consider about optimal approach to those markets since logistic costs are high. We are offering theoretical approach as well as some successful approaches to markets in Southeast Asia.